Transformasi UMKM Madu Syukri: Solusi Inovatif untuk Produksi dan Pemasaran Madu Trigona di Kota Pariaman - Wijaya, Edo Rantou; Ahmad, Nofan Hadi; Ramadhani, Indah Kurnia; Zahrina, Nadhilah; Akli, Khairul (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
Madu Syukri MSME in Pariaman produces trigona honey and faces production and marketing constraints, including excessive honey moisture content due to inadequate harvesting tools and limited product differentiation. This Community Service Program was designed to strengthen the enterprise’s value chain and market positioning. Interventions included the design of a honey dehydrator to optimize moisture levels, development of branding and labeling, packaging differentiation to enhance product positioning, and engineering of a battery- and dynamo-powered honey suction tool to increase harvesting efficiency. Activities comprised field observation, stakeholder interviews, needs assessment, and solution implementation. Results demonstrate that the dehydrator effectively reduced moisture without compromising honey quality. Branding and packaging innovations enhanced consumer appeal and market visibility, while the suction device streamlined harvesting operations. Overall, the program improved production consistency and marketing capacity, thereby increasing the competitiveness of Madu Syukri MSME in local and national markets. Findings highlight the importance of integrating technological upgrading and marketing innovation to address MSME production and market challenges.